Investigation of tensile strength on alkaline treated and untreated kenaf geotextile under dry and wet conditions. Issue 4 (August 2019) - Shirazi, Mohammad Gharehzadeh; A Rashid, Ahmad Safuan; Nazir, Ramli Bin; Abdul Rashid, Azrin Hani; Kassim, Azman; Horpibulsuk, Suksun
Abstract: Geosynthetics or geotextile is used for aggregate separation, soil reinforcement, filtration, drainage and moisture or liquid barriers in geotechnical applications. Because of the environmental issues, a bio-based material is introduced as a sustainable construction material. The kenaf fibre is a bio-based material available in the tropical countries. It can be potentially used as a geotextile because of its high tensile strength. This paper presents the tensile strength characteristics of kenaf geotextile, manufactured with and without sodium hydroxide (NaOH) treatment. The tensile strength of kenaf geotextile was determined by using the wide-width strip test based on the ASTM D4595-17 standard. Because the kenaf fibre has a high water absorption capability, the effect of wet and dry conditions on tensile behaviour of kenaf textile was studied. Two patterns of woven kenaf with two different opening sizes between their yarns (0 × 0 and 2 × 2 mm)—plain and incline patterns were studied. In addition, the tensile strength of the kenaf geotextiles, buried in natural ground, was examined after a one-year period. The tensile strength of kenaf geotextiles was higher for the smaller spaces between the yarns. Furthermore, the tensile strength and elongation were lower under wet condition. The alkaline treatment (6% concentration of NaOH) significantly improved the tensile strength of the woven kenaf geotextile. The tensile strength of the treated kenaf geotextile was higher than that of the untreated one, for both short and long-term conditions, showing the advantage of NaOH treatment.